Children's right to participation in ECEC settings: A systematic review - Correia, N.; Aguiar, C. (CREAN Conference: The impact of children's rights education and research on policy development, 2018)
The United Nations Convention on the Rights of the Child (1989) was pivotal in the definition and advocacy of children’s rights, namely children’s right to participation (Articles 12 to 17). Viewed as children’s capacity to exert influence in all matters affecting their lives, talking or acting in partnership with adults, participation can be exercised in different ways, assuming a multidimensional character (Sinclair, 2004; Stephenson, Gourley, & Miles, 2004). Distinct areas of knowledge converge on the relevance of considering children’s perspectives on their everyday lives and, specifically, in early childhood education and care (ECEC) settings (Clark & Moss, 2005). Nonetheless, few studies, measures, and empirical evidence still exist on this topic. This paper presents a systematic review of research conducted on children’s right to participation in the field of social sciences, in ECEC settings, from 1980 to 2017. More specifically, we aim to identify (a) countries and areas in which research has been conducted; (b) main definitions, theoretical backgrounds, and operationalizations of children’s right to participation; (c) type of studies (e.g., quantitative, qualitative), variables, and measures; and (d) results obtained. The search strategy is based on the ‘Preferred Reporting Items for Systematic Reviews and Meta Analyses (PRISMA) Statement’ (Liberati et al., 2009), and several databases (e.g., ERIC, PsycINFO, Scopus) were analyzed, using different combinations of words (e.g., child participation, right to participation, early childhood education), as also as inclusion and exclusion criteria (e.g., age, type of study). With this work we aim to contribute to a deeper understanding of available research on children’s right to participation. Results, implications, and future research needs will be discussed.